PENERAPAN BUDAYA RELIGIUS SEBAGAI PENGUATAN PEMBELAJARAN AKIDAH AKHLAK DI MADRASAH IBTIDAIYAH - Asifah Amaniah; Moh. Sahlan; Nuruddin; Sufraini; Tegar Setia Budi (Jurnal Ilmiah Mahasiswa Raushan Fikr, 2023)
This study investigates how Madrasah Ibtidaiyah Ar-Roudhoh in Jember integrates religious culture to strengthen Aqidah Akhlak (moral theology) education. Using qualitative, descriptive field research, data were gathered through interviews, observations, and documentation. The findings show that the implementation of religious culture at MI Ar-Roudhoh is systematically planned to enhance students' understanding of moral theology. In the classroom, activities are structured to deepen comprehension, while outside the classroom, religious practices reinforce this learning. These activities include habituation, modeling, and internalization of religious values. The result is a positive impact on students' attitudes, reflected in their cognitive, affective, and psychomotor development.